Eco-labelling and consumers: towards a re-focus and integrated approaches. (31st January 2008) - Rubik, Frieder; Frankl, Paolo; Pietroni, Lucia; Scheer, Dirk
The paper deals with voluntary environmental product information schemes, especially with eco-labels (ISO-type I labels). It distingushes direct (i.e., effects attained through the application of eco-labelling on products and services) and indirect (i.e., effects induced by eco-labelling schemes on surrounding policy, businesses and society without their visible application) effects of eco-labels. It presents an overview on the state on assessment and evaluation studies. Based on this broad picture a set of key influencing factors are introduced, two of them are general; the others are dependent on the product group. It is argued that if all factors are positive, this very likely determines the success of an eco-label Finally an integrated approach is introduced which is needed to develop effective schemes.